2007
DOI: 10.1093/annonc/mdl355
|View full text |Cite
|
Sign up to set email alerts
|

Dose-dense adjuvant chemotherapy in node-positive breast cancer: docetaxel followed by epirubicin/cyclophosphamide (T/EC), or the reverse sequence (EC/T), every 2 weeks, versus docetaxel, epirubicin and cyclophosphamide (TEC) every 3 weeks. AERO B03 randomized phase II study

Abstract: Dose-dense regimens yield more frequent and severe nonhematological toxic effects than standard dose TEC regimen. Though grade 4 toxicity rates appear acceptable with the T-->EC regimen, the incidence of grade 3-4 events makes it difficult to recommend either dose-dense regimen for further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 17 publications
4
15
1
Order By: Relevance
“…At the time of publication, at a median follow-up of 40 months, no severe safety issues were raised. As expected and in agreement with other studies [35], more patients experienced treatment delays or dose reductions with the dose-dense arm, with significantly more cycles being delivered at full dose in the conventional arm. The most common severe side-effect in our study, balanced between groups, was neutropenia, while the rate of febrile neutropenia (5%) was similar to the 2-3% rate reported in the CALGB study [9] and the 5% rate reported in the AGO study [18].…”
Section: Discussionsupporting
confidence: 91%
“…At the time of publication, at a median follow-up of 40 months, no severe safety issues were raised. As expected and in agreement with other studies [35], more patients experienced treatment delays or dose reductions with the dose-dense arm, with significantly more cycles being delivered at full dose in the conventional arm. The most common severe side-effect in our study, balanced between groups, was neutropenia, while the rate of febrile neutropenia (5%) was similar to the 2-3% rate reported in the CALGB study [9] and the 5% rate reported in the AGO study [18].…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, the RDI of AC chemotherapy was not affected by dose sequence (97% when given first vs. 98% when given second; P = 0.48). In a recent study comparing Doc?EC with EC?Doc, delivery of Doc first was associated with fewer dose delays (38% vs. 53%) and a lower incidence of Grade 4 neutropenia (29% vs. 49%) [33]. Thus it appears that the same conclusion can be drawn from all these studies, namely that providing Doc first in the chemotherapy sequence might improve delivery and decrease the incidence of adverse events when given with appropriate growth factor support.…”
Section: Discussionmentioning
confidence: 94%
“…No difference in diseasefree survival was detected between the two treatment arms (p=0.92). The limitation of anthracycline and taxane combinations is their hematologic toxicities [5,11]. Two of our patients (3%) developed treatment-related neutropenia.…”
Section: Discussionmentioning
confidence: 80%